Respiratory syncytial virus disease burden in children and adults from Latin America: a systematic review and meta-analysis - Ciapponi, Agustín (2024)
Background: Respiratory Syncytial Virus (RSV) is a common cause of lowerrespiratory tract infections (LRTI) and hospitalization worldwide. The impact of RSVin Latin America and the Caribbean (LAC) including expensive treatment options,such as palivizumab, have been extensively discussed. However, publications on theimpact of RSV disease burden in the region are scarce. This systematic review aimedto determine the incidence and prevalence of RSV in LAC by age and RSV subtype.Methods: We conducted a systematic review following Cochrane methodsto evaluate the disease burden of RSV in LAC countries. We searched studiesfrom January 2012 to January 2023 in literature databases and grey literaturewithout language restrictions. We included guidelines, observational, economic,and surveillance studies from LAC countries. Pairs of reviewers independentlyselected, and extracted data from included studies. The risk of bias was assessedusing the Study Quality Assessment Tools (NHLBI) and AGREE-II. We performedproportion meta-analyses using methods to stabilize the variance. The protocolwas registered in PROSPERO (CRD42023393731).Results: We included 156 studies, mainly from Brazil (25%), Colombia (14.5%),and Argentina (13.8%), as well as four clinical practice guidelines. Most studieswere cross-sectional (76.9%) and were classified as low risk of bias (52.6%). Themajority included inpatients (85.6%), pediatric (73.7%), and normal-risk patients(67.1%). The highest pooled prevalence was estimated in patients <1 year old(58%), with type A and B prevalence of 52 and 34%, respectively. The RSV-LRTIincidence was 15/100 symptomatic infants aged <2 years old, and the ICUadmission was 42%. The RSV-LRTI lethality was 0.6, 3% in patients aged <2 and0–5 years old, respectively, and 23% among >65 years old high-risk patients.The identified guidelines lack methodological rigor and have limitations in theirapplicability. The seasonality was more evident in South America than in CentralAmerica and The Caribbean, with a clear gap during the pandemic.Conclusion: This is the most exhaustive and updated body of evidence describing a significant burden of RSV in LAC, particularly at the extremes of life, and its seasonality patterns. Our findings could contribute could contribute facilitating effective prevention and treatment strategies for this significant public health problem.